Regulation of distinct branches of the non-canonical Wnt-signaling network in Xenopus dorsal marginal zone explants - Wallkamm, Veronika; Rahm, Karolin; Schmoll, Jana; Kaufmann, Lilian; Brinkmann, Eva-Maria; Schunk, Jessica; Kraft, Bianca; Wedlich, Doris; Gradl, Dietmar (BMC biology, 2016)
A tight regulation of the Wnt-signaling network, activated by 19 Wnt molecules and numerous receptors and co-receptors, is required for the establishment of a complex organism. Different branches of this Wnt-signaling network, including the canonical Wnt/β-catenin and the non-canonical Wnt/PCP, Wnt/Ror2 and Wnt/Ca2+ pathways, are assigned to distinct developmental processes and are triggered by certain ligand/receptor complexes. The Wnt-signaling molecules are closely related and it is still on debate whether the information for activating a specific branch is encoded by specific sequence motifs within a particular Wnt protein. The model organism Xenopus offers tools to distinguish between Wnt-signaling molecules activating distinct branches of the network.